2005
DOI: 10.1124/jpet.105.097014
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Mouse Ear Tissue Exposed to Bis-(2-chloroethyl) Sulfide: Gene Expression Profiles Correlate with Treatment Efficacy and An Established Clinical Endpoint

Abstract: Bis-(2-chloroethyl) sulfide (sulfur mustard; SM) is a potent alkylating agent. Three treatment compounds have been shown to limit SM damage in the mouse ear vesicant model: dimercaprol, octyl homovanillamide, and indomethacin. Microarrays were used to determine gene expression profiles of biopsies taken from mouse ears after exposure to SM in the presence or absence of treatment compounds. Mouse ears were topically exposed to SM alone or were pretreated for 15 min with a treatment compound and then exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Microarray analysis has become a common tool to provide such an understanding, and genomic profiling has been used to characterize transcriptional patterns in skin following various chemical exposures [12][13][14][15][16][17][18]. With respect to cutaneous bromine burns, tissue damage can progress long after exposure, thereby delaying clinical signs and symptoms, which can often lead to underestimating burn severity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Microarray analysis has become a common tool to provide such an understanding, and genomic profiling has been used to characterize transcriptional patterns in skin following various chemical exposures [12][13][14][15][16][17][18]. With respect to cutaneous bromine burns, tissue damage can progress long after exposure, thereby delaying clinical signs and symptoms, which can often lead to underestimating burn severity [5].…”
Section: Introductionmentioning
confidence: 99%
“…[45] Pre-treatment with indomethacin, in one study, was found to reduce SM-induced damage. [6] Anti-inflammatory drugs reduce the dermal, respiratory, and ocular damage caused by exposure to SM. [7] Amifostine, a radio-protective agent and its analogs have shown protection against SM toxicity in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have only been a handful of microarray studies involving analysis of mouse skin treated with sulfur mustard (Rogers et al, 2004; Sabourin et al, 2004; Dillman et al, 2006). These studies only focused on gene changes at early time points within the first 24 h post exposure.…”
Section: Introductionmentioning
confidence: 99%